Characterization of the complete chloroplast genome sequence of Blastus cochinchinensis (Melastomataceae) - Zhang, Wenchun (Mitochondrial DNA B Resour, 2019)
Blastus Lour. belongs to tribe Sonerileae (Melastomataceae), comprising about 18 species worldwide. Herein, we presented, assembled, and annotated the first complete chloroplast genome of Blastus (B. cochinchinensis). The complete chloroplast genome (cp) size of B. cochinchinensis was 156,005 bp in length, containing a pair of 26,812 bp inverted repeat (IR) regions, which were separated by a large single-copy region (LSC) 85,926 bp and a small single-copy (SSC) region 16,455 bp. The overall GC content of the genome was 37.0%. The whole genome contained 129 unique genes, including 81 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic analysis showed that B. cochinchinens was sister to Barthea barthei. The present study provided B. cochinchinensis genomic information that may be found useful in conservation and molecular phylogenetic studies on Blastus.